Oral Sub mucous fibrosis (OSMF): A Review from Ayurveda Perspective. - Kumar, Deepak; Vaghela, D B; Singh, Preetpal; Parkhi, Vishwatej (International Research Journal of Ayurveda & Yoga, 2023)
Background: Oral sub mucous fibrosis (OSMF) a chronic progressive disorder of oral cavity characterized by inflammation and progressive fibrosis of the sub mucosal tissues. Reported data published revealed an estimate of 5 million OSMF patients in India and increased over past four decades from 0.03% to 6.42%, seen commonly in younger 20-40 years age group. In Ayurvedic classical texts, no any direct references about the disease quoted, can be considered as Anukta Vyadhi (Unexplained disease) and on understanding the disease condition OSMF can be considered as Vata Pradhana Tridoshaja Mukharoga Vyadhi which needs management locally and systemically. Material and Methods: Ayurvedic literature, modern texts as well as the data web-based search engines, journal, were used to search for relevant literature and information. Result: Habit of areca nut or betel quid and tobacco chewing, excessive consumption of chilies, autoimmunity, genetic, environmental factor and dietary deficiencies are the main etiological factors. Excessive and constant use Kashaya, Katu Rasa, Ruksha, Tikshna and Ushna Dravyas, lead to Dosha Prakopa and Vikruta Dhatu formation corresponding to biochemical abnormalities/functional abnormalities and structural defects. So Vata-Pitta Pradhana Tridosha alleviating local as well as systemic treatment should be done. Conclusion: The fundamental principles of Ayurveda should be applied for achieving regain of the normalcy of oral mucosaand restoring the normal function by its preventive and curative approach.